Methodology for Assessing Innovative Entrepreneurship - Bekzhanova, T.; Yeshpanova, D.; Omarova, A.; Vorobyeva, S.; Shugaipova, Z.; Salzanova, Z. (Montenegrin Journal of Economics, 2024)
The article considers the methodology of evaluating the effectiveness of in-novative entrepreneurship, as well as criteria and indicators for evaluating innovative entrepreneurship, are considered. The definition of the word "in-novation" is given, and the specifics of the assessment of the issue under consideration depending on the levels (state, region, enterprise) are pro-vided. It is proposed to use a systematic approach when evaluating the effec-tiveness of innovative entrepreneurship. The main reasons that do not allow for a full assessment of the work of innovative entrepreneurship are listed. The subject of the study is theoretical and practical methods of assessing the innovative development of industrial enterprises. The article considers the problem that a necessary condition for improving the system of increasing the effectiveness of state policy to support small and medium-sized enter-prises is to increase the availability of financial resources.It consists of the possibility of using the proposed developments when assessing innovation activity and the current economic state of an industrial enterprise in order to determine its potential and make scientifically and practically sound deci-sions when implementing an innovation strategy. The methodology proposed in the article will allow companies to be ranked according to the level of inno-vative development, which can be applied by state statistics bodies, and in-vestors. The obtained research results can be used in teaching disciplines in the areas of "Management" and "Innovative Entrepreneurship". The devel-oped methods of assessing innovative development can be presented in the form of a computer program to improve the quality of their use in enterprises.
Keywords: Evaluation of research and development programs; small and medium-sized businesses; optimization of the portfolio of innovative projects; international experience of research evaluation; key performance indicators